Port site tuberculosis: is an epidemic on shore? - Ovi, Mir Rasekh Alam; Hossain, As Saba; Nasrin, Shamima; Salahuddin, Gazi Muhammad; Mustafa, A. S. M. Feroz; Sagar, SM Iftekhar Uddin; Hasan, Tanvir (International Surgery Journal, 2023)
Background: Bangladesh has to carry an extensive burden of tuberculosis in varied form of presentation. In the era of minimally invasive surgery (MIS) port site tuberculosis is usually a rare incidence. Among all the infections it has been identified as a prolong burden for both patients and surgeons. This study was done to notify such rare complication of MIS and tried to find out is there really an upsurge of this infection in Bangladesh. Methods: This retrospective study was done an urban area of Bangladesh during September 2020 to June 2021. 483 laparoscopic surgeries were done by six different surgeons in 5 different hospitals during September 2020 to January 2021. All surgeons have minimum five years experiences in laparoscopic surgery. 20 minutes emersion of the laparoscopic instruments into activated glutaraldehyde solution 2% (CIDEX) was used as method of chemical sterilization. Other surgical instruments were sterilized by conventional autoclave method. Results: Among them 87 patients developed port infections. 66 (75.86%) patients of this 87 developed non-healing ulcer. Biopsy from the ulcer showed granulomatous tissue in 56 patients and the other 10 was nonspecific inflammation. CAT I anti-TB chemotherapy was initiated to all the patients and all improved by this therapy. Use of 3.54% glutaraldehyde instead of 2% or immersion of instruments for a longer period (more than 20 minutes) could be tried in larger scale to prove its efficacy. Conclusions: National tuberculosis control program (NTP) should give more emphasis on cutaneous tuberculosis as the morbidity of this disease is high. Surgeons of Bangladesh should admit and report such incidences as, if it is documented in other areas of the country, it may need to develop a national guideline to prevent and treat port site tuberculosis.